Exploring the Potential of Black Shale Source Rocks in the Babouri-Figuil Basin, Northern Cameroon: A Study on Organic Petrography - Ndip, Edwin Ayuk; Maximus, Josephine (European Journal of Applied Sciences, 2023)
The Babouri-Figuil Basin is located in Northern Cameroon. Detailed studies on the organic petrology of the basin are still limited. This study analyzed a black shale sample (MF7- having Ro of 0.36% and a TOC of 22.8% ) from the basin using organic petrography to characterize the organic matter in the rock and understand its potential for hydrocarbon generation. The study found the sample to have an abundance of lipinite maceral, suggesting a Type I kerogen source rock with excellent oil-generating potential. The vitrinite reflectance of 0.36%Ro indicates that the sample is thermally immature for hydrocarbon generation. The study suggests that the sample is from a lacustrine depositional environment with relatively good access to nearby terrigenous material.